MANAJEMEN STRATEGI SEKOLAH UNGGUL - Muniroh, Musfiatul (Penerbit CV Tentrem Karya Nusa, 2018)
Competition in the increasingly competitive world of education has demanded that school administrators continue to improve the quality of their schools so that they can have excellence and different factors that are unique to the school. Therefore the importance of management strategies from school / madrasah leaders is a determinant of whether an educational institution is advanced or not, superior schools are an absolute necessity that must be owned today, so that schools continue to grow in accordance with the times, even predicting what education needs in next few years.Key Words: strategy management, superior school